2008
DOI: 10.1162/neco.2007.12-05-094
|View full text |Cite
|
Sign up to set email alerts
|

A Sensorimotor Approach to Sound Localization

Abstract: Sound localization is known to be a complex phenomenon, combining multisensory information processing, experience-dependent plasticity and movement. Here we present a sensorimotor model that addresses the question of how an organism could learn to localize sound sources without any a priori neural representation of its head related transfer function (HRTF) or prior experience with auditory spatial information. We demonstrate quantitatively that the experience of the sensory consequences of its voluntary motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 74 publications
(107 reference statements)
1
46
0
Order By: Relevance
“…6). From a computational perspective, some recent models have been developed whereby auditory spatial representations can be created by unsupervised sensorimotor learning where receiver motion is integrated with acoustic information (Aytekin et al 2008;Bernard et al 2012). Whether the motion signal is of motor (efference copy) or sensory origin (proprioception) is not known.…”
Section: Accommodation To the New Spectral Cuesmentioning
confidence: 99%
“…6). From a computational perspective, some recent models have been developed whereby auditory spatial representations can be created by unsupervised sensorimotor learning where receiver motion is integrated with acoustic information (Aytekin et al 2008;Bernard et al 2012). Whether the motion signal is of motor (efference copy) or sensory origin (proprioception) is not known.…”
Section: Accommodation To the New Spectral Cuesmentioning
confidence: 99%
“…Recently it was suggested that the ILD (interaural level difference) spectrogram carries information about the relationship between the binaural observation space and the two-dimensional (2D) localization space (azimuth and elevation) and that the latter can be retrieved via an unsupervised manifold learning method [1,2]. Within this framework, the general SSL problem is more challenging for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the computational experiments reported in [1,2] suggest the existence of a locally-linear bijection from the space of source locations to the space of binaural cues, and that the high-dimensional space spanned by the latter forms a low-dimensional manifold embedded in the former (source locations). In practice, the source-location-to-binaural-cue mapping can be approximated by a probabilistic piecewise affine mapping (PPAM) model whose parameters are learned via an EM procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been showed that such a naive agent can recover the dimensionality of physical space without any a priori knowledge [12], [13], [14]. Once the space dimensionality is known, the sensorimotor approach can also be applied to the learning of sensory space parametrization from a set of sensorimotor experiences [12], [15], [16], giving rise to spatial perception. The basic assumption is that the sensory space of the agent lies on a low-dimensional manifold whose topology is homeomorphic to the topology of the embodying space.…”
Section: Introductionmentioning
confidence: 99%
“…Following this hypothesis, the learning of spatial perception becomes the learning of such a manifold. Methods based on manifold learning have been proposed for auditory localization using supervised linear regression [17], selforganized maps [18] and within the sensorimotor approach using local tangent space alignment [15], [16].…”
Section: Introductionmentioning
confidence: 99%